2021
DOI: 10.1186/s12916-021-02054-w
|View full text |Cite
|
Sign up to set email alerts
|

Choice of HbA1c threshold for identifying individuals at high risk of type 2 diabetes and implications for diabetes prevention programmes: a cohort study

Abstract: Background Type 2 diabetes (T2D) is common and increasing in prevalence. It is possible to prevent or delay T2D using lifestyle intervention programmes. Entry to these programmes is usually determined by a measure of glycaemia in the ‘intermediate’ range. This paper investigated the relationship between HbA1c and future diabetes risk and determined the impact of varying thresholds to identify those at high risk of developing T2D. Methods We studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Remarkably, ML was capable of predicting T2DM incidence within four years, although patients who did develop T2DM and those who did not were not strikingly different in terms of their anthropometric or HbA1c data. A recent study highlighted the challenge in classifying HbA1c levels regarding the risk of developing diabetes, noting that many individuals are already classified as high-risk under current HbA1c thresholds [12]. They suggested that raising the threshold to an HbA1c value of 6.0% could improve the positive predictive value (=precision) to 12.4%.…”
Section: The Role Of Metabolites In Predicting New-onset Diabetesmentioning
confidence: 99%
“…Remarkably, ML was capable of predicting T2DM incidence within four years, although patients who did develop T2DM and those who did not were not strikingly different in terms of their anthropometric or HbA1c data. A recent study highlighted the challenge in classifying HbA1c levels regarding the risk of developing diabetes, noting that many individuals are already classified as high-risk under current HbA1c thresholds [12]. They suggested that raising the threshold to an HbA1c value of 6.0% could improve the positive predictive value (=precision) to 12.4%.…”
Section: The Role Of Metabolites In Predicting New-onset Diabetesmentioning
confidence: 99%
“…These reports are in line with the findings in our cohorts (Figure 3). Approaches to adjust the diagnostic threshold of HbA 1c (24)(25)(26) or to combine FPG and HbA 1c for screenings were not real breakthroughs (5). Consequently, a considerable number of individuals with prediabetes remain undiagnosed using the available and recommended diagnostic parameters for prediabetes screening.…”
Section: Malementioning
confidence: 99%
“…The measurement of HbA1c was performed by a physician or paramedic (Yes = HbA1c  6.5% and No = HbA1c <6.5%). (38) 21 C…”
Section: Laboratory Analysismentioning
confidence: 99%